Extraction of collagen from by-products of Amazonian fish tambaqui, Colossoma macropomum and pirarucu Arapaima gigas - Alexandre Augusto Barai; Antônio José Inhamuns; Tiago Cabral Nóbrega; Cristiane Cunha Guimarães; Lígia dos Santos Mourão; Antonio Fabio Lopes de Souza; Fagnaldo Braga Pontes; Flávia Dayane Félix Farias; Joana Maia Mendes; João Paulo Ferreira Rufino; Adriano Teixeira de Oliveira (Applied Food Research)
Several high-value commercial products, such as collagen, have been developed from by-products of the fish processing industry due to their wide range of applications and importance for human health. This study aimed to extract, determine the yield, and characterize the collagen obtained from the scales of Colossoma macropomum and Arapaima gigas. The samples underwent two treatments: uncrushed scales (T1) and crushed scales (T2). The moisture content in tambaqui scales showed average values of 47.71 % (T1) and 12.63 % (T2), while lipid content was 1.39 % (T1) and 1.33 % (T2). Protein content was 41.04 % (T1) and 72.95 % (T2). For pirarucu, higher values were observed for ash (28.80 % in T1), lipids (1.06 % in T1), and protein (48.40 % in T2), while higher moisture content was recorded for T1 (28.54 %). The collagen extraction yields for C. macropomum and A. gigas were 2.97 % and 1.48 % for T1, and 1.51 % and 0.85 % for T2, respectively. FTIR and XRD analyses confirmed that the collagens extracted from both species are primarily composed of type I collagen. These findings contribute to biotechnological research by adding value to the by-products of these two commercially important species in the Amazon Region of Brazil.